Understanding the light soaking effects in inverted organic solar cells functionalized with conjugated macroelectrolyte electron-collecting interlayers - Xu, Weidong; Xia, Ruidong; Ye, Tengling; Zhao, Li; Kan, Zhipeng; Mei, Yang; Yan, Congfei; Zhang, Xinwen; Lai, Wenyong; Keivanidis, Panagiotis E.; Huang, Wei (My University, 2016)
Three kinds of charged star-shaped conjugated macroelectrolytes, named as PhNBr, TPANBr, and TrNBr, are synthesized as electron-collecting interlayers for inverted polymer solar cells (i-PSCs). Based on these well-defined structured interlayer materials, the light soaking (LS) effect observed in i-PSCs was studied systematically and accurately. The general character of the LS effect is further verified by studying additional i-PSC devices functionalized with other common interlayers. The key-role of UV photons was confirmed by electrochemical impedance spectroscopy and electron-only devices. In addition, the ultraviolet photoelectron spectroscopy measurements indicate that the work function of the indium tin oxide (ITO)/interlayer cathode is significantly reduced after UV treatment. In these i-PSC devices the LS effect originates from the adsorbed oxygen on the ITO substrates when oxygen plasma is used however, even a small amount of oxygen from the ambient is also enough for triggering the LS effect, albeit with a weaker intensity. Our results suggest that the effect of adsorbed oxygen on ITO needs to be considered with attention while preparing i-PSCs. This is an important finding that can aid the large-scale manufacturing of organic solar cells via printing technologies, which do not always ensure the full protection of the device electrode substrates from oxygen.
Keywords: Cathode interlayer; Conjugated polyelectrolytes; Inverted solar cells; Light soaking effect; Star‐shaped molecules